NH2-UiO-66 (at) BTT-BPDA core-shell material as well as preparation method and application thereof
By designing NH2-UiO-66@BTT-BPDA core-shell material, the thermal stability, regenerative and adsorption performance of existing adsorbents when treating industrial wastewater is solved, and efficient adsorption and easy regeneration wastewater treatment effects are achieved.
Patent Information
- Application Number
- CN202411754838.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-03
AI Technical Summary
When treating industrial wastewater, existing adsorbents have problems such as low thermal stability, poor regenerativeness, poor adsorption performance and complex preparation process, making it difficult to effectively remove harmful substances in complex wastewater.
A core-shell material of NH2-UiO-66@BTT-BPDA was designed. By using NH2-UiO-66 as the core and BTT-BPDA as the shell, it uses carbon-nitrogen covalent bonds to form a stable porous crystalline core-shell hybrid material for the treatment of industrial wastewater.
The material exhibits high efficiency of adsorbing iodine and organic dyes at room temperature, with fast adsorption rate, good selectivity, and easy to regenerate. It is suitable for treating industrial wastewater with high salt content, high colority and high toxicity.
Smart Images

Figure CN119798583A_ABST
Abstract
Description
Technical field:
[0001] The present invention belongs to the field of adsorbent materials, and specifically relates to an NH2-UiO-66@BTT-BPDA core-shell material and a preparation method and application thereof. Background technology:
[0002] With the rapid development of industrialization, water pollution is still a serious problem that endangers public health and the environment. The chemical industry (such as pesticides, dyes, pharmaceuticals, coke and surfactants, etc.) has a wide range of products, complex reactions, and uses a large number of harmful raw materials, such as halogen compounds, nitro compounds, etc., which leads to complex pollutant components in wastewater, large organic pollutant content, high salt content, high chroma, high toxicity and difficult to degrade. The treatment method based on biodegradation can no longer meet the current situation of modern industrial development. Adsorption is considered to be an effective sewage treatment technology because of its low cost, simple operation, environmental friendliness, simple regeneration, and large-scale application. However, existing adsorbents often have the defects of low thermal stability, poor regeneration, poor adsorption performance, and complex preparation process.
[0003] COFs have the advantages of low mass density, high thermal stability, permanent porosity and large specific surface area, and are one of the materials used for industrial wastewater treatment; MOFs, as another organic porous material, is a good candidate for constructing heterostructures with COFs to improve the performance of monomers. MOF / COF composite materials not only inherit their own characteristics such as rich porous structure, ultra-high porosity and large specific surface area, but also often show unexpected new properties through the synergistic effect of various components, thus showing great application potential in different fields such as membrane separation, sensing and catalysis. However, the research on this type of composite materials in the field of solid phase extraction needs further exploration. Therefore, the preparation of an adsorbent of MOF@COF composite material is of great significance for the treatment of industrial wastewater. Summary of the invention:
[0004] In view of this, the present invention designs the NH2-UiO-66@BTT-BPDA core-shell material and uses it for the treatment of industrial wastewater. It has low preparation cost, good structural stability, high adsorption capacity for iodine and organic dyes, fast adsorption rate, good selectivity, and easy regeneration.
[0005] A NH2-UiO-66@BTT-BPDA core-shell material has NH2-UiO-66 (MOF) as a core, BTT-BPDA (COF) as a shell, and carbon-nitrogen covalent bonds as the connection between the core and the shell; wherein the core-shell material is an octahedral porous crystalline core-shell hybrid material.
[0006] A method for preparing NH2-UiO-66@BTT-BPDA core-shell material, the method specifically comprising:
[0007] Step 1: preparing NH2-UiO-66: placing zirconium tetraoxide and 2-aminoterephthalic acid in N,N-dimethylamide and mixing evenly, adding acetic acid solution dropwise to obtain a first premixed liquid; placing the first premixed liquid in an oven and heating it at 120° C. for 24 hours, separating the heated first premixed liquid into a solid-liquid state, washing the solid product three times with a mixture of methanol and N,N-dimethylamide, and drying it in an oven at 70° C. for 12 hours, and drying the solid product to obtain the NH2-UiO-66;
[0008] Step 2: Formaldehyde formation of NH2-UiO-66: the NH2-UiO-66 and benzotrithiophene tricarboxaldehyde are mixed in dioxane to obtain a second premixed solution, the second premixed solution is heated in an oven at 110° C. for 72 hours, and the solid and liquid products are separated by centrifugation after natural cooling to room temperature, the solid product is washed with tetrahydrofuran and dried in an oven at 70° C. for 12 hours to obtain formaldehyded NH2-UiO-66;
[0009] Step 3: Preparation of NH2-UiO-66@BTT-BPDA core-shell material: dissolve the aldehyde-modified NH2-UiO-66, benzotrithiophene tricarboxaldehyde and (2,2'-bipyridine)-5,5'-diamine in a glass bottle containing dioxane and glacial acetic acid; heat the glass bottle at 110°C for three days to obtain a brown product; centrifuge the brown product, wash the solid product with anhydrous tetrahydrofuran and vacuum dry it at 70°C for 12 hours to obtain a brown solid powder, namely, the NH2-UiO-66@BTT-BPDA core-shell material.
[0010] During the reaction, MOF first reacts with benzotrithiophene tricarboxaldehyde to cover the octahedron on the surface of the MOF core with -CHO groups, and then the -CHO groups react with the -NH2 groups to cover the core with the BTT-BPDA-COF shell through the Schiff base reaction.
[0011] Preferably, in step 1, the molar ratio of zirconium tetrachloride to 2-aminoterephthalic acid is (0.5-1.5):(0.5-1.5); and the volume ratio of N,N-dimethylformamide to acetic acid is (8-12):(0.5-1.6).
[0012] Preferably, the mass ratio of NH2-UiO-66 and benzotrithiophene tricarboxaldehyde in step 2 is (1.5-2.5):(0.5-1.5).
[0013] Preferably, the molar ratio of (2,2'-bipyridine)-5,5'-diamine to benzotrithiophene tricarboxaldehyde in step 3 is (2-4):(1-3), the mass ratio of the aldehyded NH2-UiO-66 to benzotrithiophene tricarboxaldehyde is (2-6):(0.5-1.5); the volume ratio of glacial acetic acid to dioxane is (0.5-1.5):(10-20).
[0014] An application of NH2-UiO-66@BTT-BPDA core-shell material is to
[0015] NH2-UiO-66@BTT-BPDA core-shell material is used for the adsorption of harmful substances in industrial wastewater.
[0016] Preferably, the industrial wastewater is dye wastewater or iodine-containing wastewater.
[0017] Preferably, the application is specifically as follows: dispersing the NH2-UiO-66@BTT-BPDA core-shell material in industrial wastewater, oscillating and adsorbing until adsorption equilibrium is reached; the core-shell material that has reached adsorption equilibrium can be regenerated. Generally, the regeneration method is specifically as follows: soaking the dye-adsorbed NH2-UiO-66@BTT-BPDA core-shell adsorbent in alcohol, ultrasonically oscillating for 20-40 minutes for desorption, and then washing with deionized water and centrifuging to complete the regeneration of the NH2-UiO-66@BTT-BPDA core-shell adsorbent.
[0018] Preferably, the dye wastewater is one of methylene blue, crystal violet, malachite green, rhodamine B and methyl orange wastewater.
[0019] COFs have the advantages of low mass density, high thermal stability, permanent porosity and large specific surface area, and are one of the materials with the greatest application potential in environmental pollution control. Compared with traditional adsorbents, the ordered pore structure of COFs provides abundant adsorption sites, which accelerates the rapid diffusion of pollutants. In addition, the pore size and shape of COFs are easy to adjust, which makes it possible to separate different pollutants. At the same time, COFs have high chemical and thermal stability. The low density of COFs means that they have high adsorption capacity. MOFs, as another organic porous material, can be a good candidate for constructing heterojunctions with COFs to improve the performance of monomers. MOF / COF composites not only inherit their own characteristics such as rich porous structure, ultra-high porosity and large specific surface area, but also often show unexpected new properties through the synergistic effect of each component. The present invention designs a novel method for rapidly preparing NH2-UiO-66@BTT-BPDA core-shell composite material. The building blocks of the prepared composite material are connected by dynamic carbon-nitrogen covalent bonds, and the structure has good stability. At the same time, the building blocks are rich in high-density benzene rings and pyridine rings, and have the advantages of high adsorption capacity, fast adsorption rate, good selectivity, and easy regeneration for iodine and organic dyes. The dye adsorbent prepared by the preparation method of the present invention has a simple method for treating dye wastewater, and does not need to adjust the reaction temperature, and can be carried out at room temperature. There is no need to strictly adjust the pH value of the wastewater, and a good removal effect is achieved in a wide pH range from acidic to alkaline; at the same time, the efficiency of the composite material for iodine adsorption is compared with pure MOFs, and the adsorption amount per unit time is greater. Description of the drawings:
[0020] Attached Figure 1 Schematic diagram of the synthesis of the composite material in Example 1.
[0021] Attached Figure 2 This is the FT-IR spectrum of NH2-UiO-66@BTT-BPDA in Example 1.
[0022] Attached Figure 3 This is a SEM image of the MOF in Example 1.
[0023] Attached Figure 4 This is the SEM image of NH2-UiO-66@BTT-BPDA in Example 1.
[0024] Attached Figure 5 This is the TEM image of NH2-UiO-66@BTT-BPDA in Example 1.
[0025] Attached Figure 6 This is the N element mapping diagram of NH2-UiO-66@BTT-BPDA in Example 1.
[0026] Attached Figure 7 This is the S element mapping diagram of NH2-UiO-66@BTT-BPDA in Example 1.
[0027] Attached Figure 8 This is the Zr element mapping diagram of NH2-UiO-66@BTT-BPDA in Example 1.
[0028] Attached Fig. 9 This is the dye removal rate diagram using NH2-UiO-66@BTT-BPDA as adsorbent.
[0029] Attached Fig.10 This is the adsorption amount of iodine using NH2-UiO-66@BTT-BPDA as the adsorbent. Specific implementation method:
[0030] In order to make the technical solution of the present invention easier to understand, the technical solution of the present invention is now clearly and completely described in the form of specific embodiments.
[0031] Embodiment 1:
[0032] In this embodiment, a method for preparing a NH2-UiO-66@BTT-BPDA core-shell material comprises the following steps:
[0033] (1) Preparation of NH2-UiO-66 material:
[0034] 0.045mmol zirconium tetrachloride and 0.045mmol 2-aminoterephthalic acid were dissolved in 1.2mL acetic acid and 10mL N, N-dimethylformamide, respectively, and placed in a 20mL glass bottle. After ultrasonication for 30 minutes, the vial was sealed and heated in an oven at 120°C for 24 hours. After centrifugation, the product was washed three times with a mixture of methanol and N, N-dimethylformamide (volume ratio of 1:4), and then vacuum dried at 70°C for 12 hours to obtain NH2-UiO-66 crystals with an octahedral structure.
[0035] (2) Aldehyde-NH2-UiO-66 material:
[0036] 20 mg NH2-UiO-66 was added to a glass bottle containing 8 mL 1,4-dioxane and ultrasonically treated for 10 min to obtain a suspension. 10 mg benzotrithiophene tricarboxaldehyde was then added to the suspension and ultrasonically treated for 30 min to obtain a second suspension. 0.5 mL glacial acetic acid was added to the second suspension, heated in an oven at 110 ° C for 72 h, cooled naturally to room temperature, and then centrifuged to separate the solid and liquid products. The solid product was washed with tetrahydrofuran and dried in an oven at 70 ° C for 12 hours to obtain the NH2-UiO-66@BTT composite material, marked as U@BTT.
[0037] (3) Preparation of NH2-UiO-66@BTT-BPDA core-shell materials:
[0038] The synthesized 0.026g U@BTT was added to a glass vial containing 8mL 1,4-dioxane to obtain a suspension, and the suspension was ultrasonically dispersed for 5 minutes. 0.02mmol benzotrithiophene tricarboxaldehyde and 0.03mmol (2,2'-bipyridine)-5,5'-diamine were dispersed in the suspension and ultrasonically treated for 30min to obtain a second suspension. 0.5mL glacial acetic acid was added to the second suspension and heated in an oven at 110℃ for 72h. The solid and liquid products were separated by centrifugation, the solid product was washed with tetrahydrofuran and vacuum dried at 70℃ for 12h to obtain NH2-UiO-66@BTT-BPDA core-shell material.
[0039] Embodiment 2:
[0040] In this embodiment, a method for preparing a NH2-UiO-66@BTT-BPDA core-shell material comprises the following steps:
[0041] (1) Preparation of NH2-UiO-66 material:
[0042] 0.023mmol zirconium tetrachloride and 0.068mmol 2-aminoterephthalic acid were dissolved in 1.6mL acetic acid and 8mL N, N-dimethylformamide, respectively, and placed in a 20mL glass bottle. After ultrasonication for 30 minutes, the vial was sealed and heated in an oven at 120°C for 24 hours. After centrifugation, the product was washed three times with a mixture of methanol and N, N-dimethylformamide (volume ratio of 1:4), and then vacuum dried at 70°C for 12 hours to obtain NH2-UiO-66 crystals with an octahedral structure.
[0043] (2) Aldehyde-NH2-UiO-66 material:
[0044] 15 mg NH2-UiO-66 was added to a glass bottle containing 8 mL 1,4-dioxane and ultrasonically treated for 10 min to obtain a suspension. 15 mg benzotrithiophene tricarboxaldehyde was then added to the suspension and ultrasonically treated for 30 min to obtain a second suspension. 0.5 mL glacial acetic acid was added to the second suspension, heated in an oven at 110 ° C for 72 h, cooled naturally to room temperature, and then centrifuged to separate the solid and liquid products. The solid product was washed with tetrahydrofuran and dried in an oven at 70 ° C for 12 hours to obtain the NH2-UiO-66@BTT composite material, marked as U@BTT.
[0045] (3) Preparation of NH2-UiO-66@BTT-BPDA core-shell materials:
[0046] The synthesized 0.04g U@BTT was added to a glass vial containing 10mL 1,4-dioxane to obtain a suspension, and the suspension was ultrasonically dispersed for 5 minutes. 0.03mmol benzotrithiophene tricarboxaldehyde and 0.02mmol (2,2'-bipyridine)-5,5'-diamine were dispersed in the suspension and ultrasonically treated for 30min to obtain a second suspension. 0.25mL glacial acetic acid was added to the second suspension and heated in an oven at 110℃ for 72h. The solid and liquid products were separated by centrifugation, the solid product was washed with tetrahydrofuran and vacuum dried at 70℃ for 12h to obtain NH2-UiO-66@BTT-BPDA core-shell material.
[0047] Embodiment 3:
[0048] In this embodiment, a method for preparing a NH2-UiO-66@BTT-BPDA core-shell material comprises the following steps:
[0049] (1) Preparation of NH2-UiO-66 material:
[0050] 0.068mmol zirconium tetrachloride and 0.023mmol 2-aminoterephthalic acid were dissolved in 0.5mL acetic acid and 12mL N, N-dimethylformamide, respectively, and placed in a 20mL glass bottle. After ultrasonication for 30 minutes, the vial was sealed and heated in an oven at 120°C for 24 hours. After centrifugation, the product was washed three times with a mixture of methanol and N, N-dimethylformamide (volume ratio of 1:4), and then vacuum dried at 70°C for 12 hours to obtain NH2-UiO-66 crystals with an octahedral structure.
[0051] (2) Aldehyde-NH2-UiO-66 material:
[0052] 25 mg NH2-UiO-66 was added to a glass bottle containing 8 mL 1,4-dioxane and ultrasonically treated for 10 min to obtain a suspension. 5 mg benzotrithiophene tricarboxaldehyde was then added to the suspension and ultrasonically treated for 30 min to obtain a second suspension. 0.5 mL glacial acetic acid was added to the second suspension, heated in an oven at 110 ° C for 72 h, cooled naturally to room temperature, and then centrifuged to separate the solid and liquid products. The solid product was washed with tetrahydrofuran and dried in an oven at 70 ° C for 12 hours to obtain the NH2-UiO-66@BTT composite material, marked as U@BTT.
[0053] (3) Preparation of NH2-UiO-66@BTT-BPDA core-shell materials:
[0054] The synthesized 0.01g U@BTT was added to a glass vial containing 5mL 1,4-dioxane to obtain a suspension, and the suspension was ultrasonically dispersed for 5 minutes. 0.01mmol benzotrithiophene tricarboxaldehyde and 0.04mmol (2,2'-bipyridine)-5,5'-diamine were dispersed in the suspension and ultrasonically treated for 30min to obtain a second suspension. 0.5mL glacial acetic acid was added to the second suspension and heated in an oven at 110℃ for 72h. The solid and liquid products were separated by centrifugation, the solid product was washed with tetrahydrofuran and vacuum dried at 70℃ for 12h to obtain NH2-UiO-66@BTT-BPDA core-shell material.
[0055] Figure 2 This is the FT-IR spectrum of the NH2-UiO-66@BTT-BPDA composite material prepared in Example 1. It can be seen from the figure that the typical characteristic peaks of the NH2-UiO-66@BTT-BPDA hybrid material are similar to the characteristic peaks of NH2-UiO-66. -1 The characteristic peaks are derived from the C=N stretching vibration of BTT-BPDA.
[0056] Figure 3 This is the SEM image of NH2-UiO-66 prepared in Example 1. As shown in the figure, the structure of MOF is octahedral and the surface is smooth.
[0057] Figure 4 This is the SEM image of the NH2-UiO-66@BTT-BPDA composite material prepared in Example 1. Figure 5 This is the TEM image of NH2-UiO-66@BTT-BPDA. It can be seen from the figure that there is an obvious shell structure on the surface of NH2-UiO-66, so the NH2-UiO-66@BTT-BPDA core-shell structure was successfully synthesized.
[0058] Figure 6-8 This is the mapping diagram of the NH2-UiO-66@BTT-BPDA composite material prepared in Example 1. The Zr element of MOF is evenly distributed, and the N and S elements of BTT-BPDA cover the entire structure, which further confirms that the NH2-UiO-66@BTT-BPDA core-shell structure with BTT-BPDA shell and NH2-UiO-66 core structure is successfully synthesized.
[0059] Application Example 1:
[0060] The NH2-UiO-66@BTT-BPDA core-shell adsorption material (5 mg) prepared in Example 1 was dispersed in 5 mL of dye wastewater to be treated (malachite, green rhodamine b, methylene blue, methyl orange, crystal violet), and the dye concentration was 50 μM. The conical flask containing the NH2-UiO-66@BTT-BPDA core-shell adsorption material and the dye mixture was placed on an oscillator, and the flask was taken out after oscillation at a speed of 190 r / min for 30 minutes, and then filtered with a water filter head. The filtered solution was then detected in an ultraviolet spectrophotometer, and the initial concentration and the concentration after adsorption of the dye were obtained according to the standard curve between the absorbance and the concentration of each dye; the removal rate of NH2-UiO-66@BTT-BPDA for different dyes was calculated, and the results are as follows: Fig. 9 .
[0061] The obtained NH2-UiO-66@BTT-BPDA core-shell adsorbent exhibited excellent adsorption effect on methyl orange, malachite green, and rhodamine B dyes, with a removal rate of 99%, a removal rate of 90% for crystal violet, and a removal rate of 65% for methylene blue.
[0062] Application Example 2:
[0063] The NH2-UiO-66@BTT-BPDA core-shell adsorption material (10 mg) and iodine (200 mg) prepared in Example 1 were respectively placed in different glass bottles (this application example explores the adsorption performance of iodine by the NH2-UiO-66@BTT-BPDA core-shell adsorption material prepared in Example 1 by directly adsorbing iodine), and then the two glass bottles were placed in the same wide-mouth bottle. After sealing the bottle mouth, it was placed in an oven at a temperature of 75°C and a pressure of normal pressure. After 0 to 100 hours, it was taken out and the mass after adsorption was weighed to calculate the adsorption amount. The result is as follows Fig.10 .
[0064] The adsorption capacity of iodine by the obtained NH2-UiO-66@BTT-BPDA core-shell adsorbent was 167%, which was much higher than the adsorption capacity of the original MOF (67%).
[0065] Table 1 Comparison of adsorption performance of the adsorbent prepared in Example 1 and other adsorbents
[0066]
[0067] As shown in Table 1, NH2-UiO-66@BTT-BPDA has a higher adsorption capacity for a variety of dyes than other adsorbents, indicating that the composite material synthesized in this study has excellent adsorption performance. In addition, the adsorption performance of the composite material for iodine is also better than that of existing adsorbents. Therefore, NH2-UiO-66@BTT-BPDA has application value in adsorbing dyes in actual high-concentration wastewater.
[0068] It should be noted that the embodiments described herein are only partial embodiments of the present invention, rather than all implementations of the present invention, and the embodiments are only exemplary, and their role is only to provide a more intuitive and clear way to understand the content of the present invention, rather than to limit the technical solutions described in the present invention. Without departing from the concept of the present invention, all other implementation methods that can be thought of by ordinary technicians in this field without creative work, and other simple replacements and various changes to the technical solutions of the present invention, all belong to the protection scope of the present invention.
Claims
1. A NH2-UiO-66@BTT-BPDA core-shell material, characterized in that: The core-shell material has NH2-UiO-66 as the core, BTT-BPDA as the shell, and carbon-nitrogen covalent bonds as the connection between the core and the shell; wherein the core-shell material is an octahedral porous crystalline core-shell hybrid material.
2. A method for preparing NH2-UiO-66@BTT-BPDA core-shell material, characterized in that: The method is specifically as follows: Step 1: preparing NH2-UiO-66: placing zirconium tetraoxide and 2-aminoterephthalic acid in N,N-dimethylamide and mixing evenly, adding acetic acid solution dropwise to obtain a first premixed liquid; placing the first premixed liquid in an oven and heating it at 120° C. for 24 hours, separating the heated first premixed liquid into a solid-liquid state, washing the solid product with a mixture of methanol and N,N-dimethylamide, and drying the solid product to obtain NH2-UiO-66; Step 2: Formaldehyde formation of NH2-UiO-66: the NH2-UiO-66 and benzotrithiophene tricarboxaldehyde are mixed uniformly in dioxane to obtain a second premixed solution, the second premixed solution is placed in an oven and heated at 110° C. for 72 hours, cooled to room temperature, and then centrifuged to separate solid and liquid products, the solid product is washed with tetrahydrofuran and dried to obtain formaldehyded NH2-UiO-66; Step 3: Preparation of NH2-UiO-66@BTT-BPDA core-shell material: dissolve the aldehyde-modified NH2-UiO-66, benzotrithiophene tricarboxaldehyde and (2,2'-bipyridine)-5,5'-diamine in a glass bottle containing dioxane and glacial acetic acid; heat the glass bottle at 110°C for three days to obtain a brown product; centrifuge the brown product, wash the solid product with anhydrous tetrahydrofuran and vacuum dry to obtain a brown solid powder, which is the NH2-UiO-66@BTT-BPDA core-shell material.
3. The method for preparing a NH2-UiO-66@BTT-BPDA core-shell material according to claim 2, characterized in that: In step 1, the molar ratio of zirconium tetrachloride to 2-aminoterephthalic acid is (0.5-1.5):(0.5-1.5); the volume ratio of N,N-dimethylformamide to acetic acid is (8-12):(0.5-1.6).
4. The method for preparing a NH2-UiO-66@BTT-BPDA core-shell material according to claim 2, characterized in that: In step 2, the mass ratio of NH2-UiO-66 to benzotrithiophene tricarboxaldehyde is (1.5-2.5):(0.5-1.5).
5. The method for preparing a NH2-UiO-66@BTT-BPDA core-shell material according to claim 2, characterized in that: In step 3, the molar ratio of the (2,2'-bipyridine)-5,5'-diamine to benzotrithiophene tricarboxaldehyde is (2-4):(1-3), the mass ratio of the aldehyded NH2-UiO-66 to benzotrithiophene tricarboxaldehyde is (2-6):(0.5-1.5); the volume ratio of the glacial acetic acid to dioxane is (0.5-1.5):(10-20).
6. An application of NH2-UiO-66@BTT-BPDA core-shell material, characterized in that: The NH2-UiO-66@BTT-BPDA core-shell material is used for the adsorption of harmful substances in industrial wastewater.
7. The use of a NH2-UiO-66@BTT-BPDA core-shell material as claimed in claim 6, characterized in that: The industrial wastewater is one of dye wastewater and iodine-containing wastewater.
8. The use of a NH2-UiO-66@BTT-BPDA core-shell material as claimed in claim 6, characterized in that: The application is specifically as follows: dispersing the NH2-UiO-66@BTT-BPDA core-shell material in industrial wastewater, and oscillating and adsorbing until adsorption equilibrium is reached.
9. The use of a NH2-UiO-66@BTT-BPDA core-shell material as claimed in claim 7, characterized in that: The dye wastewater is one of methylene blue, crystal violet, malachite green, rhodamine B and methyl orange wastewater.
Citation Information
Patent Citations
Solid-phase microextractor and preparation method thereof
CN114019068A
Preparation of benzotrithienyl covalent organic photocatalytic material connected with dipyridyl group and application of benzotrithienyl covalent organic photocatalytic material in photocatalytic full-decomposition of water
CN115646545A
Conjugated two-dimensional polymer film as well as preparation method and application thereof
CN116239759A
Cited By
Core-shell structure MOF material capable of selectively adsorbing rhenium and preparation method and application of rhenium adsorbing material
CN120939919A